Random analysis of train-bridge coupled system under non-uniform ground motion - Zhao, Han; Wei, Biao; Guo, Peidong; Tan, Jincheng; Xiang, Ping; Jiang, Lizhong; Fu, Wenchu; Liu, Xiang (Advances in structural engineering, 2023)
The increasing prevalence of simply supported bridges in high-speed railway (HSR) lines has raised concerns about the safety of trains crossing these bridges during an earthquake. As these bridges are typically continuous and long, it is essential to consider the effects of traveling seismic waves on the random vibration of the train-bridge coupled (TBC) system. To address this issue, the new point estimate method (NPEM) is used to analyze the dynamic response and parametric sensitivity of a three-dimensional TBC system subjected to non-uniform ground motion with multiple random parameters. The motion equations of the TBC system are derived using bridge seismic theory under multi-support excitations. The analysis incorporates random variables such as the damping ratio, density, Young’s modulus, and seismic magnitude to capture the influence of traveling seismic waves on the random vibration of the TBC system. Simulation results show that the traveling seismic wave effect can cause changes in the first vibration frequencies of the train and bridge, potentially leading to the first few frequencies reordering. Additionally, considering the traveling wave effect will make the TBC system’s response less apparent than without considering the traveling wave effect. The uncertainty of bridge and seismic parameters can seriously affect the train’s running safety. The sensitivity of the bridge density and seismic magnitude is particularly prominent for bridge responses when the traveling seismic waves effect is strong. This methodology can be used for random and sensitivity analysis of a train running over a long bridge under non-uniform earthquake conditions. Overall, the NPEM can provide valuable insights into the dynamic behavior and safety of TBC systems, enabling more effective design and maintenance of HSR bridges.